Effect of using intensive exercise my way and distributor of random to learn some skills goalkeepers in soccer - Abdul Hussein, Mohammed (Journal of Physical Education, 2012)
Included the first door on the definition of research and its importance was addressed to the research problem and the reason for the use of these methods and to identify the objectives of the research and homework and the three fields. The second section to include on theoretical studies and similar research on the subject. Part III to include addressed to the research methodology and appointed by the user and how to divide the groups with equal sample and the exploratory experiment, the researcher then turned to the pretest and the main experiment to search and then post-test and statistical tools used in the research. Part IV to include address to view the findings of the researcher then analyzed and discussed, which were identified to the importance of teaching methods used in research to develop some skills of soccer goalkeepers, then discussed the amount of learning each of the two sets of induction. The Title V to contain the conclusions and recommendations reached by the researcher, and was one of the most important conclusions that the methods of teaching (intensive and distributor) the impact of positive and effective learning some skills goalkeeping soccer with a clear preference for a way of learning distributor, the most important recommendations are the use of learning method distributor random with beginner students to learn the skills of soccer goalkeepers, and the use of intensive learning with random students more advanced in learning.